Involvement of casein kinase 1 epsilon/delta (Csnk1e/d) in the pathogenesis of familial Parkinson's disease caused by CHCHD2 - Satoru Torii; Satoko Arakawa; Shigeto Sato; Kei‐ichi Ishikawa; Daisuke Taniguchi; Hajime Tajima Sakurai; Shinya Honda; Yuuichi Hiraoka; Masaya Ono; Wado Akamatsu; Nobutaka Hattori; Shigeomi Shimizu (EMBO Molecular Medicine)
Abstract Parkinson's disease (PD) is a common neurodegenerative disorder that results from the loss of dopaminergic neurons. Mutations in coiled‐coil‐helix‐coiled‐coil‐helix domain containing 2 (CHCHD2) gene cause a familial form of PD with α‐Synuclein aggregation, and we here identified the pathogenesis of the T61I mutation, the most common disease‐causing mutation of CHCHD2. In Neuro2a cells, CHCHD2 is in mitochondria, whereas the T61I mutant (CHCHD2T61I) is mislocalized in the cytosol. CHCHD2T61l then recruits casein kinase 1 epsilon/delta (Csnk1e/d), which phosphorylates neurofilament and α‐Synuclein, forming cytosolic aggresomes. In vivo, both Chchd2T61I knock‐in and transgenic mice display neurodegenerative phenotypes and aggresomes containing Chchd2T61I, Csnk1e/d, phospho‐α‐Synuclein, and phospho‐neurofilament in their dopaminergic neurons. Similar aggresomes were observed in a postmortem PD patient brain and dopaminergic neurons generated from patient‐derived iPS cells. Importantly, a Csnk1e/d inhibitor substantially suppressed the phosphorylation of neurofilament and α‐Synuclein. The Csnk1e/d inhibitor also suppressed the cellular damage in CHCHD2T61I‐expressing Neuro2a cells and dopaminergic neurons generated from patient‐derived iPS cells and improved the neurodegenerative phenotypes of Chchd2T61I mutant mice. These results indicate that Csnk1e/d is involved in the pathogenesis of PD caused by the CHCHD2T61I mutation.